Evaluation of Scoring Systems for Airway Management After Oral Cancer Surgery: A Retrospective Study. (August 2021) - Abe, Atsushi; Umemura, Eri; Hayashi, Hiroki; Ito, Yu; Adachi, Moriyasu
Objective: Postoperative airway obstruction following oral cancer surgery is difficult to predict. Scoring systems used to assess the need for tracheotomy use risk factors as criteria. We aimed to examine whether these clinical scoring systems can predict airway obstruction following oral cancer surgery. Methods: We assessed 95 patients who underwent oral cancer surgery without tracheotomy under general anesthesia between January 2007 and April 2019. We reviewed multiple factors from the patients' medical records, including age, sex, tumor site, body mass index, tumor stage, type of surgery, airway management method, Cameron and Gupta scores, and postoperative airway complications. Results: Tumors were located in the maxilla ( n  = 14), buccal mucosa ( n  = 13), mandible ( n  = 14), floor of the mouth ( n  = 6), and tongue ( n  = 48). Twenty-seven patients (28.4%) were graded as Stage 1, 37 patients (38.9%) as Stage 2, 9 patients (9.5%) as Stage 3, and 3 (3.2%) patients as Stage 4. Nine patients (9.5%) had local recurrences, and ten patients (10.5%) had neck metastases. Postoperative oxygen administration alone failed to improve dyspnea in 4 patients (4.2%). The median Cameron scores between patients with and without airway trouble were not significantly different ( P  = 0.226). However, a significant difference was observed in median Gupta scores between patients with and without airway trouble ( P  = 0.01). We created a receiver operating characteristic curve to predict postoperative airway trouble based on the preoperative Gupta score; the area under the curve was 0.856 (95% confidence interval: 0.61-1). A Gupta score cutoff value of 3.0 had a sensitivity of 92.3% and specificity of 75.0%. Conclusions: Screening based on the Gupta score appears to be effective in predicting postoperative airway obstruction. We propose that this screening tool can be used to better plan tracheotomy and other airway management strategies during preoperative patient assessment.